Launched north approach viaduct in the new Queensferry crossing, UK: design and construction. Issue 2 (19th October 2018) - Bernardo, Hector; Thompson, Steve; Vazquez, Antonio; Ward, Alan; Taylor, David; Bullingham, Jennifer
Abstract : Launching is a bridge erection method that provides significant advantages when there is difficult underdeck access for falsework, crane and heavy plant. In such cases, assembling the deck in a more accessible position and launching it over the piers may mean a significant saving of resources. In some cases access is simply not possible due to other constraints, for example over environmentally protected areas. This is the case of the north approach viaduct of the new Queensferry Crossing, a major cable-stayed bridge over the Firth of Forth in Scotland, UK. This paper provides a description of the approach viaduct north and its launch process. This viaduct is a single/twin-girder bridge with composite section and two spans of 101·5 m and 104 m. Owing to its particular characteristics and impressive launch weight of 6200 t, the launching process has not been conventional, and particular solutions have been used and combined to ensure full compliance with the strict design constraints. The assembly process was not conventional either, owing to space constraints and the weight and size of the pieces.